A strategic energy efficiency overview for sustainable business development: Case study Coca-Cola industry - Cara, Rezarta; Korsita, Bajram; Cara, Msc. Fjona (International Journal of Innovative Research and Scientific Studies, 2025)
This paper investigates the role of energy efficiency as a strategic tool for sustainable business development, with a particular focus on the Coca-Cola industry. A qualitative methodology was employed, incorporating case studies, quantitative analysis, and a literature review to examine the economic and environmental advantages of energy-efficient practices in large-scale manufacturing. Investments in energy efficiency result in financial returns, risk reduction, and regulatory compliance. Companies benefit from reduced costs, improved brand image, and competitive advantages through sustainability initiatives. Energy efficiency serves as both a business and environmental strategy that fosters innovation and sustainability, thereby contributing to long-term growth. By adopting energy-efficient practices, businesses, especially those in energy-intensive industries, can decrease costs, enhance energy resilience, and bolster their market position.